Collaborative Governance dalam Tata Kelola Pariwisata-Desa (Studi Pariwisata-Desa â€œBumiaji Agrotourismâ€ di Kota Wisata Batu) - Matthoriq, Matthoriq; Zauhar, Soesilo; Hermawan, Romy (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
The objective of this research is examines the role of collaborative governance in rural tourism development, especially in the tourist area of